Whose trades convey information? Evidence from a cross-section of traders - Lukas Menkhoff; Maik Schmeling (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper contributes empirically to our understanding of informed traders. It analyzes traders? characteristics in an electronic limit order market via anonymous trader identities. We use six indicators of informed trading in a cross-sectional multivariate approach to identify traders with high price impact. More information is conveyed by those traders? trades who?simultaneously?use medium-sized orders (practice stealth trading), have large trading volume, are located in a financial center, trade early in the trading session, at times of wide spreads and when the order book is thin.
Keywords: F31; G12; D82; G15; 330; Market microstructure; informed trading; trade size; foreign exchange